Remaking the Mosaic: Religious Leaders and Secular Borders in the Colonial Levant - Henley, Alexander D. M. (Religion and society, 2015)
The colonial view of Levantine society as a mosaic of religions established lasting precedents for communal self-governance and power sharing in modern states. Yet it ironically disguises the extent to which the region's religious geography was reimagined by colonial rule. Principles of religious freedom and minority rights combined with a perception of "oriental religions" to create a unique and powerful place for religious leaders to govern. The borders that would define national societies in Palestine-Israel, Lebanon, and Syria also remade the boundaries by which the religious mosaic was structured. This article will highlight institutional change in the Maronite Christian and Sunni Muslim communities, showing how each reformulated its religious leadership in response to the creation and enforcement of Lebanon's borders with Palestine and Syria from 1920 to 1948. The "traditional" religious leaderships of today are in no small part products of the same colonial "lines in the sand" within which nations were formed.